2012
DOI: 10.1038/emboj.2011.503
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling identifies epigenetic dysregulation in pancreatic islets from type 2 diabetic patients

Abstract: DNA methylation profiling identifies epigenetic dysregulation in pancreatic islets from type 2 diabetic patientsThe first genome-scale DNA methylation study on pancreatic islets from type 2 diabetic patients identifies disease-associated DNA methylation pattern that translate into aberrant gene expression in novel factors relevant for β-cell function and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
293
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(321 citation statements)
references
References 156 publications
19
293
3
2
Order By: Relevance
“…Although modest in absolute magnitude, the widespread DNA methylation changes induced by HFO in this study are quantitatively similar to those previously reported to be influenced by HFO in selected candidate genes implicated in growth and metabolic disease, including type 2 diabetes [14,16,18,22,23]. However, the extent to which general epigenetic changes play a role in the short-term regulation of metabolic functions in muscle by HFO, including IR, remains to be established.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although modest in absolute magnitude, the widespread DNA methylation changes induced by HFO in this study are quantitatively similar to those previously reported to be influenced by HFO in selected candidate genes implicated in growth and metabolic disease, including type 2 diabetes [14,16,18,22,23]. However, the extent to which general epigenetic changes play a role in the short-term regulation of metabolic functions in muscle by HFO, including IR, remains to be established.…”
Section: Discussionsupporting
confidence: 85%
“…However, the extent to which general epigenetic changes play a role in the short-term regulation of metabolic functions in muscle by HFO, including IR, remains to be established. The functional read-out of altered DNA methylation has traditionally been thought to involve altered mRNA expression, and significant correlations between DNA promoter methylation and distinct gene expression has previously been reported in some [13,15] but not all human studies, including the Human Epigenome Project, supporting the notion that the relationship between DNA methylation and gene expression is not always straightforward [14,16,24]. Few significant correlations were observed between DNA The top three common diseases and disorders are presented according to hypomethylated, hypermethylated and both hypo-and hypermethylated CpG sites/genes methylation and gene expression levels for a number of candidate genes in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the Paired box 4 (PAX4) gene, which is necessary for the formation of mature b-cells, is hypermethylated and silenced in islets from patients with T2DM. 19,20 Vice versa, Arista-less-related homeobox (ARX), a master gene for a-cells, is normally methylated and repressed in pancreatic b-cells by DNMT1 with concomitant preservation of b-cell identity. 21 Therefore, it has been proposed that b-cell identity depends on the epigenetically controlled antagonistic activities of PAX4 and ARX, but the fine tuning mechanisms are still unclear.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…CpG loci affiliated to 254 gene promoters displaying significant differential DNA methylation in diabetic pancreatic islets (Volkmar et al, 2012).…”
Section: Hyperglycemiamentioning
confidence: 99%